CNS-drug design - Smith, Quentin (Henry Stewart Talks, 2008)
Central nervous system diseases, Drug market for CNS disorders, Traditional CNS drug targets, Novel CNS drug targets, Multiple obstacles for drug delivery to CNS, Pathways for drug exchange within the CNS, The structure of brain capillaries impedes uptake, Measures of drug uptake and distribution in brain, BBB permeability and solute lipid solubility, Tissues capillary PS and 95% equilibration time, Cerebral blood flow affects drug uptake and Kin, Initial uptake vs. steady-state distribution, Plasma protein binding and brain drug uptake, Brain capillary drug transporters, Transporters and drug distribution across BBB, "Enzymatic" blood-brain barrier, Relation between bound and free drug, Free drug distribution ratio at steady state, BBB changes in pathology and disease, Drug-like properties to cross the BBB, Early findings in BBB drug uptake, Measures of lipophilicity, Passive permeability across lipid membranes, Drug ionization, Influence of pH on neutral fraction, Lipinski "rule of five", Impact of hydrogen bonds and alkyl groups, Positive CNS drugs, Poor CNS drug, in vitro measures, In vivo measures, Methods to improve brain uptake, Simple rules for efflux transporters, % drug distribution to brain, Biologic compounds, Brain pharmacokinetics
Archived at 2018/05/31